The Effect of Digital Payment QR Code Implementation and Digital Service Knowledge on Consumer Satisfaction of Mypertamina Application Users (Case Study: SPBU Pertamina 54,691,03) - Qurrotul A’yun; Octaviana Arisinta (Global Action and Education for Society, 2025)
Digital transformation has experienced rapid advancement, particularly in payment processes and increasingly sophisticated data storage systems. This development is not only limited to the information technology sector, but has also expanded to various other sectors, including the energy sector such as subsidized fuel distribution. This study aims to determine the influence of QR code implementation, digital payment, digital service knowledge, and service quality on consumer satisfaction among users of the MyPertamina application at SPBU Pertamina 54.691.03. This research employed a non-probability sampling technique with purposive sampling and involved 55 respondents who use the MyPertamina application. Data were collected through online and offline questionnaires, then analyzed using multiple linear regression with IBM SPSS version 21. The results show that QR code implementation, digital payment, digital service knowledge, and service quality have a significant influence both partially and simultaneously on consumer satisfaction among MyPertamina application users at SPBU Pertamina 54.691.03. With a coefficient of determination (R²) value of 0.861, it is evident that these four variables explain 86.1% of the variation in consumer satisfaction, while the remaining 13.9% is influenced by other factors not included in this study. These findings indicate that technological transformation, accompanied by enhanced digital service knowledge, can facilitate the management of subsidized fuel data, improve payment efficiency, and support better service quality, thereby strengthening the positive consumer experience and increasing satisfaction among MyPertamina application users.